Cultural and geological heritage in time elapsed during historical Kingdoms in Yogyakarta Special Region, Indonesia - Mulyaningsih, Sri (Berita Sedimentologi, 2021)
Yogyakarta, Indonesia is known for its kingdom government system for all its living history; since 8-10th century Mataram Hindu-Buddhist temples to the present Muslim Ngayogyokarto Hadiningrat. Those stretch of history resulted in many artefacts and chronicles. A cultural imaginary line that linking Merapi Volcano in the north and the Indian Ocean in the south through the Yogyakarta Palace in the middle has a sacral geo-cultural heritage, explaining a prosperity gentle volcanic town, a beautiful scheme of the open panoramic features with several temples standing on the plain and mountainous landscapes in between the rest of earthquakes and the volcanic eruptions. Many temples were partly buried under volcanic materials, and some others show evidence of being shaken several times by earthquakes. Boulders of volcanic materials varying in size and shapes are present in the plain of Yogyakarta, near Cangkiringan, Ngemplak and Ngaglik. Landslides exposed many geological features, such as faults, rock formation and stratigraphy, and some unstable slopes. Cultural and geological heritages at Yogyakarta Region were created over the time.